Perceived parental rearing styles and depression in Chinese adolescents: the mediating role of self-compassion - Ren, Yanzhen; Zhang, Shining; Huang, Caiying; Zhang, Jie; Jiang, Tingyun; Fang, Yuan (Frontiers in Psychiatry, 2024)
Background: Adolescence is a period characterized by rapid biological and psychological change, and adolescents have a heightened risk of depression. Parental rearing is an important influencing factor for depression in adolescence. However, the mechanism of influence needs further exploration.Methods: A total of 1839 adolescents were recruited from a junior and a senior high school in Zhongshan City, Guangdong Province, China. They were requested to completed the Parental Bonding Instrument (PBI), Self-Compassion Scale (SCS), and Depression Anxiety and Stress Scale-21(DASS-21).Results: Adolescents recalled their mothers as being more caring and controlling than their fathers. Parental care (maternal care, paternal care) and parental encouragement of autonomy (maternal encouragement of autonomy, paternal encouragement of autonomy) were both negative predictors of depression, while parental control (maternal control, paternal control) was positive predictor of depression. Self-compassion mediated all relationships between parental rearing styles (parental care, parental encouragement of autonomy, and parental control) and depression but played different mediating roles (complete or incomplete mediating role) in different relationships.Self-compassion plays a mediator role in all relationships between perceived parental rearing styles (parental care, parental encouragement of autonomy, and parental control) and depression. Adolescents who grown up with less parental care, less parental encouragement of autonomy, and high parental control deserve special attention. Educators and clinicians could help those adolescents reduce the occurrence of depression by increasing their level of self-compassion.